Granular composition comprising graphene and sulfur and method for producing same
By using a granular composition of 50-95% sulfur and 5-50% graphene nanosheets, the problem of poor cathode conductivity of lithium-sulfur batteries is solved, and the battery performance is improved and the preparation process is simplified.
Patent Information
- Application Number
- CN202380060216.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-25
- Filing Date
- 2023-08-23
- Publication Date
- 2025-04-11
AI Technical Summary
Because sulfur is not conductive, the cathode of the lithium-sulfur battery is reduced to the surface where sulfur particles come into contact with the electrolyte, affecting the energy density and performance of the battery.
Using a granular composition containing 50-95% sulfur, 5-50% graphene nanosheets and optional binder, mixing by a turbine mixer device at a specific temperature and circumferential speed to form a granular composition that does not require grinding.
The conductivity and performance of the battery cathode is improved, the energy density and stability of the lithium-sulfur battery is improved, and the preparation method is simple and does not require grinding, which reduces processing time.
Abstract
Description
[0001] The present invention relates to a granular composition comprising graphene, sulfur and optionally a binder, and a method for producing the granular composition. The present invention also relates to a dispersion of the granular composition in a liquid medium and the use of the dispersion for producing a battery cathode. Background Art
[0002] The development of high energy density rechargeable batteries is currently of great commercial interest. There are many systems such as lithium-ion batteries that can equip portable electronic systems, Ni-MH batteries that can equip hybrid vehicles, or other technologies.
[0003] Lithium-sulfur or Li-S batteries are considered a promising alternative to lithium-ion batteries. The interest in this type of battery stems from the high energy density potential of sulfur. In addition, sulfur has the advantages of being abundant, cheap and non-toxic, which makes the concept of large-scale development of Li-S batteries possible.
[0004] The discharge and charge mechanisms of Li-S batteries are based on the oxidation-reduction of sulfur at the cathode. and lithium oxidation-reduction at the anode
[0005] In order for the reaction to occur quickly at the electrodes, the cathode and anode must be good electron conductors. However, since sulfur is an electrical insulator, it must be made conductive in order to achieve a high-performance cathode.
[0006] When a lithium-sulfur battery cell is discharged, the sulfur in the cathode is reduced. Since sulfur does not conduct electricity, the reduction is limited to the surface of the sulfur particles that are in contact with the electrolyte.
[0007] Various attempts have been made to improve the electrical contact between sulfur particles and the electrolyte; in fact, it is known that sulfur or other sulfur-containing materials can be mixed with conductive materials such as carbon black in order to increase their conductivity.
[0008] However, in this manner, the specific energy of the lithium-sulfur cell decreases as the total weight of the cell increases.
[0009] Additionally, attempts have been made to grind sulfur and conductive materials together to form a mixture of fine particles to improve the contact area between the conductive particles.
[0010] However, too fine a particle size may destroy the porosity of the entire electrode. Summary of the invention
[0011] It is therefore an object of the present invention to provide a granular composition comprising sulphur for producing a battery cathode which improves the properties of the cathode and thus of the battery using the cathode.
[0012] The granular composition has a substantially regular and controllable morphology, which can be dispersed in water or in an organic solvent without prior adaptation to a specific type of dispersion, ie it is suitable for use as is in both water-based dispersions and solvent-based dispersions.
[0013] Another object of the present invention is to provide a process for preparing a granular composition comprising sulphur which is simple, efficient and "mill-free", ie which does not require one or more milling steps in a mill, thereby significantly reducing the processing time.
[0014] Another object of the present invention is to provide a dispersion of a granular composition comprising a granular material and one or more additives in water or an organic solvent to enable the manufacture of a battery cathode.
[0015] It is yet another object of the present invention to provide improved battery cathodes.
[0016] Thus, one aspect of the present invention relates to a granular composition comprising:
[0017] a) 50 to 95% by weight of sulfur;
[0018] b) 5 to 50 wt % of graphene nanoplatelets;
[0019] At least 90% of the graphene nanosheets have lateral dimensions (x, y) of 50 nm to 20,000 nm and a thickness (z) of 1 nm to 50 nm and a C / O ratio of ≥35:1.
[0020] Preferably, the composition further comprises 0.5 to 35 wt % of a binder.
[0021] In another embodiment, the composition according to the invention further comprises 0.5% to 35% by weight of a particulate material selected from pigments and fillers.
[0022] Another aspect of the present invention provides a method for preparing a granular composition comprising:
[0023] a) 50% to 95% by weight of a particulate material selected from pigments and fillers;
[0024] b) 5 to 50 wt% of graphene nanoplatelets having lateral dimensions (x, y) of 50 to 20,000 nm, a thickness (z) of 1 to 50 nm, and a C / O ratio of ≥ 35:1;
[0025] c) optionally 0.5 to 35 wt % of a binder;
[0026] wherein the sulfur, the graphene nanosheets and optionally the binder are mixed in a turbine mixer device; the method is carried out at a temperature of 20°C to 150°C, the turbine mixer device being provided with at least one impeller wherein the blades rotate at a circumferential speed of 4m / sec to 50m / sec.
[0027] According to another aspect, the present invention relates to a dispersion of the granular composition defined above in a liquid chosen from water and an organic solvent.
[0028] Yet another aspect of the present invention relates to the use of a granular composition or dispersion as described above for the manufacture of a battery cathode.
[0029] According to another aspect, the present invention relates to a battery cathode comprising the above composition. DETAILED DESCRIPTION
[0030] In its most general aspect, the invention relates to a composition in granular form comprising graphene, sulfur, optionally one or more binders and optionally one or more pigments and / or fillers for providing a battery cathode with improved performance.
[0031] According to the invention, the sulfur is preferably sulfur in elemental form.
[0032] According to the present invention, the binder is a wetting dispersant that reduces the interfacial tension between the particulate material and the graphene nanoplatelets and the interfacial tension between the particulate composition and the liquid (water or organic solvent) in which the particulate composition is dispersed.
[0033] The granular composition of the present invention comprises a digital electromagnetic sieve vibrator Vibration Mode FTL0200 (Digital Electromagnetic Sieve Shaker Vibration mod. FTL0200) measures particles with a particle size of 10 μm to 4000 μm.
[0034] In the present specification, the term "particle size" means a value representing the average size of particles, ie, the volume size of particles in the form of clusters (defined herein as "granules") .
[0035] The volume-based size of a particle is equal to the diameter of an ideal sphere that would contain the given particle inside. In particular, when using sieve analysis, the diameter of the ideal sphere corresponds to the sieve mesh size. Volume-based sizing of particles with digital electromagnetic sieve shakers Vibration mode FTL0200 measurement.
[0036] According to one aspect of the present invention, the granular composition comprises a digital electromagnetic sieve vibrator. The vibration mode FTL0200 measures particles with sizes ranging from 100 μm to 3000 μm.
[0037] According to one aspect of the present invention, the granular composition comprises a digital electromagnetic sieve vibrator. The vibration mode FTL0200 measures particles with a size of 500μm to 3000μm.
[0038] According to one aspect of the present invention, the granular composition is substantially free of nano-sized solid particulate material, in particular it is free of solid particulate material with a size less than 1 μm, which would generate dust and cause environmental problems, wherein the term "free" means that solid particulate material with a size less than 1 μm is not present or is present in an amount of not more than 5% by weight.
[0039] According to one aspect of the present invention, the granular composition comprises:
[0040] a) 50 to 95% by weight of sulfur;
[0041] b) 5 to 50 wt % of graphene nanoplatelets;
[0042] At least 90% of the graphene nanosheets have lateral dimensions (x, y) of 50 nm to 20,000 nm and a thickness (z) of 1 nm to 50 nm and a C / O ratio of ≥35:1.
[0043] Preferably, the granular composition comprises:
[0044] a) 86 to 92% by weight of sulfur;
[0045] b) 8 to 14 wt. % of graphene nanoplatelets.
[0046] The composition according to the invention also comprises 0.5 to 35% by weight of a binder.
[0047] Preferably, the composition comprises from 1.5% to 6% binder.
[0048] According to one aspect of the invention, at least 90% of the graphene nanosheets have lateral dimensions (x, y) of 80 nm to 15000 nm.
[0049] According to one aspect of the present invention, at least 90% of the graphene nanosheets have a thickness (z) of 3 nm to 20 nm.
[0050] According to one aspect of the invention, at least 90% of the graphene nanosheets have a C / O ratio of ≥ 45:1.
[0051] According to one aspect of the invention, at least 90% of the graphene nanosheets have lateral dimensions (x, y) of 100 nm to 10000 nm.
[0052] According to one aspect of the invention, at least 90% of the graphene nanosheets have a thickness (z) of 5 nm to 15 nm.
[0053] According to one aspect of the invention, at least 90% of the graphene nanosheets have a C / O ratio of ≥50:1.
[0054] In this specification, the size of the graphene nanoplatelets is defined with reference to a system of Cartesian axes x, y, z, it being understood that the particles are essentially flat plates, but may also have irregular shapes. In any case, the lateral dimensions and thicknesses set with reference to the x, y and z directions must be understood as the maximum dimension in each of the aforementioned directions.
[0055] The structural characterization of graphene can be performed using the test method ISO / TS21356-1,202103.
[0056] Structural characterization of the graphene incorporated in the compositions of the present invention can be performed by separating the graphene from the particulate material (ie, pigment or filler), from the binder, and from any other components of the composition by methods known to those skilled in the art.
[0057] Graphene is a material consisting of a single atomic layer of hybridized carbon atoms in the sp2 form. They are therefore arranged in a highly crystalline and regular, closely spaced hexagonal honeycomb structure.
[0058] In the scientific and patent literature, different methods for preparing graphene are disclosed, such as chemical vapor deposition, epitaxial growth, chemical exfoliation and chemical reduction of the oxidized form of graphene (GO).
[0059] The applicant Directa Plus SpA is the holder of patents and patent applications related to methods for producing structures comprising graphene layers, such as EP 2 038 209 B1, EP 3 157 864 B1 and 3 157 865 B1. The last two patents mentioned describe methods for producing pristine graphene dispersions from which graphene nanosheets of the size required for implementing the present invention can be obtained.
[0060] Pristine graphene, i.e., with a C / O ratio ≥ 35 and having the dimensional characteristics defined above, is manufactured by Directa Plus SpA under the trademark Production and sales.
[0061] The C / O ratio of the graphene used in the composition according to the present invention is determined by elemental analysis using an elemental analyzer (CHNS O) that provides weight percentages of various elements.
[0062] When a more precise determination is needed, a transmission electron microscope (TEM) combined with energy dispersive X-ray spectroscopy (TEM-EDX) is used to determine the C / O ratio. This is a combination of two effective techniques, and as with SEM, the microscopic surface structure of the sample can be seen with high precision and more closely than with conventional optical microscopes. The resolution of a scanning electron microscope can be less than 1 nm, which is much higher than an optical microscope. Therefore, a more precise and higher quality image of the surface topography of the sample is obtained. Alternatively, a TEM (i.e., a transmission electron microscope) can be used instead of a SEM.
[0063] When it is desired to determine the elemental composition of a sample, an EDX detector is connected to a SEM or TEM instrument. The EDX detector identifies the elements present in the sample and determines their concentration and distribution. This allows for the precise determination of C and O.
[0064] According to the embodiment described in the above patent document, the method for producing graphene is continuously performed: a graphite sheet is continuously fed to a high-temperature expansion step; the expanded graphite thus obtained is continuously discharged in an aqueous medium, and the expanded graphite dispersed in the aqueous medium is continuously subjected to an exfoliation and size reduction treatment by a method of ultrasonic treatment and / or high-pressure homogenization.
[0065] As described in these patent documents, the final dispersion of graphene nanosheets obtained can be concentrated or dried, depending on the desired final form of the graphene.
[0066] In cases where liquids are undesirable or uncontrollable at a process level, or where water cannot be used due to chemical incompatibility, the purpose of drying the dispersion is to obtain a dry powder that is easily redispersible in various matrices (both solvents and polymers).
[0067] A significant advantage of the production method described in the aforementioned patent document is the possibility of operating without the use of surfactants. In fact, the graphene nanosheets thus obtained can be pristine, both due to the high C / O ratio and due to the absence of foreign matter such as surfactants that could contaminate them. In fact, it has been found that, in the absence of surfactants, it is possible to obtain graphene having a conductivity significantly higher than that of the graphene obtained in the case of a method using a surfactant. This improves the performance of graphene in a variety of applications.
[0068] Graphene nanosheets having the above-defined lateral dimensions, thickness (z), and C / O ratio have high thermal conductivity.
[0069] The binder of the granular composition of the present invention is a wetting dispersant selected from the following:
[0070] The content of modified polyurethane is 100% polyurethane oligomer and polyurethane polymer;
[0071] Nonionic surfactants, including fatty acid ethoxylates, alcohol ethoxylates and ethoxylated sorbitan esters, preferably free of alkylphenol ethoxylates (APEO) and volatile organic compounds (VOCs), including sorbitan monooleate;
[0072] Anionic surfactants, preferably free of alkylphenol ethoxylates (APEO) and volatile organic compounds (VOC); covering sodium polynaphthalene methane sulfonate, polymers with ethylene oxide, sodium polyphosphate, sodium salt of polyacrylic acid;
[0073] Phosphate esters and their salts, including 6EO and 9EO tridecyl phosphate;
[0074] Aldehyde and ketone resins;
[0075] Epoxidized soybean oil;
[0076] Polyethers modified with ester groups of phosphoric acid and its salts;
[0077] Fatty acid modified polyesters;
[0078] Polymers and copolymers having pigment-affinity groups, including modified polyethers having groups with high pigment affinity;
[0079] 2,5-Furandione, telomers with 1,1'-(1,1-dimethyl-3-methylene-1,3-propanediyl)bis(benzene) and vinylbenzene, 3-(dimethylamino)propyl imide, imide with polyethylene glycol 2-aminopropyl Me ether, 2-[(C10-16-alkoxy)methyl]oxirane-quaternized benzoate;
[0080] Sodium polycarboxylate;
[0081] A mixture of 5-chloro-2-methyl-2H-isothiazol-3-one and 2-methyl-2H-isothiazol-3-one (CASN° 55965-84-9).
[0082] As regards the APEO- and VOC-free nonionic surfactants, these preferably have a pH of 5 to 7 and a viscosity of up to 100 s, the latter measured in accordance with standard DIN EN ISO 2431 (flow cup 6 mm, 23° C.).
[0083] As regards the aldehyde and ketone resins, mention may be made, for example, of the products marketed by BASF, such as It has an average molecular weight of 800 to 2000 Da and a melting point of 70 to 130 °C.
[0084] As regards copolymers having pigment-affinic groups, examples are the products sold under the brand Byk 2055 by BYK-Chemie.
[0085] As regards alkylphenol-free nonionic wetting emulsifiers, mention may be made of the product sold under the brand Nuosperse FN265 by Elementis.
[0086] The above-mentioned types of binders have a high affinity with the sulfur and graphene forming the granular composition of the present invention. They ensure the stability of the sulfur particles and graphene nanosheets forming the composition, thereby also stabilizing the granules of the composition. In addition, the binder stabilizes the dispersion of the granules in the composition.
[0087] According to the invention, the composition may also comprise from 0.5% to 35% by weight of a particulate material chosen from pigments and fillers.
[0088] According to the present specification, the term "particulate material" means a pigment or filler in the form of solid particles or powder.
[0089] According to the invention, pigments and fillers are substances or compounds that absorb part or all of the spectrum and reflect the complementary part, thus forming a visible color.
[0090] According to the present invention, the particulate material as defined above is combined with graphene nanosheets, and optionally with a binder, and optionally with other additives, and manufactured into a composition in granular form suitable for further processing to obtain the desired battery cathode.
[0091] Thus, a particulate material is a material that, if combined with graphene and manufactured in a particulate form, has properties that are beneficial to the composition.
[0092] According to another aspect of the present invention, the solid particulate material is a filler.
[0093] Preferably, the filler is selected from calcium carbonate, kaolin, mica, talc, silica, preferably fumed silica, barium sulfate and any combination of these elements. According to one aspect of the present invention, the filler consists of calcium carbonate.
[0094] The composition according to the invention may also contain carbon black, nanotubes, graphite.
[0095] The granular composition according to the invention can be prepared by mixing the components in a turbine mixer apparatus.
[0096] The turbine mixer device is a high shear granulator, which comprises: a cylindrical container with at least one inlet and at least one outlet; an optional heating and / or cooling jacket for bringing and / or maintaining the temperature inside the container to a predetermined temperature. A rotating shaft with at least one impeller provided with blades is mounted inside the container in a chamber. The container is closed by a top cover. A schematic partial diagram of the device is shown in Figures 1A, 1B and 1C, which do not show the top cover.
[0097] The granular material, graphene nanoplatelets and binder are introduced into a turbine mixer device as shown in Figure 1A. The impeller is rotated so that the blades reach a peripheral speed of 4 to 50 m / sec. Mixing occurs at a temperature of 20 to 150°C.
[0098] The device moves the mixture of graphene, binder and pigment and / or filler from the static phase and pushes it to form a vortex similar to a tornado (which is enclosed inside a cylindrical chamber), starting to rotate from the bottom of the chamber to the top in a spiral, as shown in Figure 1B. Then due to the barrier provided by the top cover, the mixture collapses toward the center of the chamber by gravity, as shown in Figure 1C, and the mixture falls toward the lower part of the container, where it is once again pushed upward and outward to form an ascending spiral. This effect creates a vortex that ensures the mixing and aggregation of particles, thereby allowing the formation of dust-free and well-flowing granules.
[0099] The presence of an impeller that cuts off the flow of the vortex and stops the advancement of the particles ensures the dispersion of any microclusters, thus guaranteeing an optimal dispersion of the graphene and its uniform distribution inside the granules.The mechanical energy from the mixing / aggregation is converted into heat energy via the rotation and shearing action performed by the vortex.
[0100] Preferably, the rotating shaft comprises 1 to 7 impellers, more preferably 4 impellers, mounted in series on the rotating shaft.
[0101] Preferably, the turbine mixer apparatus includes a heating and / or cooling jacket to control the temperature of the chamber in which the components are mixed.
[0102] Preferably, the temperature is from 30°C to 150°C, more preferably from 60°C to 120°C.
[0103] Preferably, the process is carried out for a total time of 5 minutes to 60 minutes.
[0104] According to one aspect of the invention, the binder is gradually (ie, continuously in real time) introduced into the turbine mixer.
[0105] According to one aspect of the invention, the preparation of the composition of the invention occurs discontinuously, for example in batch mode rather than in continuous mode.
[0106] According to one aspect of the invention, the process for preparing the composition of the invention is carried out without using any solvent, ie it is a substantially dry process. The term "dry" means that the amount of liquid in the process does not exceed 5% by weight of the entire composition.
[0107] In particular, the term "solvent" means a substance or mixture of substances that is capable of dissolving or dispersing other substances and is liquid at room temperature (i.e., 20°C to 40°C), such as a non-polar solvent, an aprotic polar solvent, a protic polar solvent or any mixture thereof, including a diluent that has no solubilizing effect on any component of the mixture.
[0108] According to one aspect, the present invention relates to a dispersion of the granular composition defined above in a liquid selected from water and an organic solvent, wherein the term "solvent" has the same meaning as above.
[0109] The compositions defined above are suitable for use as such to produce water-based dispersions and solvent-based dispersions. These dispersions (if the amount of liquid is relatively small, they can also be defined as "pastes") are further processed to produce battery cathodes.
[0110] The examples listed below illustrate some embodiments of the invention and are provided by way of non-limiting examples.
[0111] Example
[0112] The apparatus used for preparing the granular composition of the invention is a turbine mixer having a container with a volume of 20 liters equipped with 4 impellers.
[0113] The graphene consists of nanoplatelets manufactured by Directa Plus SpA, with the particle sizes indicated in the examples below.
[0114] Example 1
[0115] Composition: S: 85% GNP: 10% Binder: 5%
[0116] 5300 g of powdered elemental sulfur was mixed and ground with 600 g of pure G+ (Directa Plus) pure graphene nanoplatelet powder. The graphene contained graphene nanoplatelets, at least 90% of which had a lateral dimension of less than 9905 nm and a thickness (z) D90 of 8 nm, and the C / O ratio of the graphene was 40:1.
[0117] 300 g of the wetting agent DisperByk 2013 (Byk) were added to both components.
[0118] The dry grinding equipment was a 20 1 discontinuous equipment equipped with 4 rotors. Considering the explosive properties of sulphur powder, the chamber was kept in an inert atmosphere (nitrogen) for the entire preparation time.
[0119] Process parameters: 20 minutes at a peripheral speed of 23 m / s; temperature reached 75°C.
[0120] The particle size of the obtained granules was: <1500 μm.
[0121] Example 2
[0122] Composition: S: 85GNP: 10% Binder: 5%
[0123] 5300 g of powdered elemental sulfur was mixed and ground with 600 g of pure G+ (Directa Plus) pure graphene nanoplatelet powder. The graphene contained graphene nanoplatelets, at least 90% of which had a lateral dimension of less than 9905 nm and a thickness (z) D90 of 8 nm, and the C / O ratio of the graphene was 50:1.
[0124] 300 g of the wetting agent DisperByk 2055 (Byk) were added to both components.
[0125] The dry grinding equipment was a 20 1 discontinuous equipment equipped with 4 rotors. Considering the explosive properties of sulphur powder, the chamber was kept in an inert atmosphere (nitrogen) for the entire preparation time.
[0126] Process parameters: 20 minutes at a peripheral speed of 23 m / s; temperature reached 75°C.
[0127] The particle size of the obtained granules was: <1500 μm.
[0128] Example 3
[0129] 5300 g of powdered elemental sulfur was mixed and ground with 600 g of pure G+ (Directa Plus) pure graphene nanoplatelet powder. The graphene contained graphene nanoplatelets, at least 90% of which had a lateral dimension of less than 9905 nm and a thickness (z) D90 of 8 nm, and the C / O ratio of the graphene was 75:1.
[0130] 300 g of the wetting agent Tween 80 (Croda) were added to both components.
[0131] The dry grinding equipment was a 20 1 discontinuous equipment equipped with 4 rotors. Considering the explosive properties of sulphur powder, the chamber was kept in an inert atmosphere (nitrogen) for the entire preparation time.
[0132] Process parameters: 20 minutes at a peripheral speed of 23 m / s; temperature reached 75°C.
[0133] The particle size of the obtained granules was: <1500 μm.
[0134] Example 4
[0135] Composition: S: 86.3% GNP: 10.7% Binder: 3%
[0136] 5178g of powdered elemental sulfur was mixed and ground with 642g of pure G+ (Directa Plus) pure graphene nanoplatelet powder. The graphene contained graphene nanoplatelets, at least 90% of which had a lateral dimension of less than 9905nm and a thickness (z) D90 of 8nm, and the C / O ratio of the graphene was 85:1.
[0137] 180 g of the wetting agent Atmer 110 (Croda) were added to both components.
[0138] The dry grinding equipment was a 20 1 discontinuous equipment equipped with 4 rotors. Considering the explosive properties of sulphur powder, the chamber was kept in an inert atmosphere (nitrogen) for the entire preparation time.
[0139] Example 5
[0140] Composition: S: 86.3% GNP: 10.7% Binder: 3%
[0141] 5178g of powdered elemental sulfur was mixed and ground with 642g of pure G+ (Directa Plus) pure graphene nanoplatelet powder. The graphene contained graphene nanoplatelets, at least 90% of which had a lateral dimension of less than 9905nm and a thickness (z) D90 of 8nm, and the C / O ratio of the graphene was 100:1.
[0142] 180 g of the wetting agent DisperByk 2055 (Byk) were added to both components.
[0143] The dry grinding equipment was a 20 1 discontinuous equipment equipped with 4 rotors. Considering the explosive properties of sulphur powder, the chamber was kept in an inert atmosphere (nitrogen) for the entire preparation time.
[0144] Example 6
[0145] Composition: S: 89% GNP: 11%
[0146] 5340 g of powdered elemental sulfur was mixed and ground with 660 g of pure G+ (Directa Plus) pure graphene nanoplatelet powder. The graphene contained graphene nanoplatelets, at least 90% of which had a lateral dimension of less than 9905 nm and a thickness (z) D90 of 8 nm, and the C / O ratio of the graphene was 90:1.
[0147] The dry grinding equipment was a 20 1 discontinuous equipment equipped with 4 rotors. Considering the explosive properties of sulphur powder, the chamber was kept in an inert atmosphere (nitrogen) for the entire preparation time.
[0148] Example 7
[0149] The graphene formulation of Example 1 was used to prepare an aqueous dispersion containing 58.4 wt% of the additive of the example. 510.73 g of deionized water was placed in a container and the additive was added during stirring. 716.91 g of the additive was added. The dispersion was produced using a DISPERMAT CN 40 apparatus equipped with a VMA60 Cowles head set to rotate at 4000 rpm. The additive was added in 3 batches of about 238 g each; after each addition of the additive, the disperser was rotated at 4000 rpm for 4 minutes.
[0150] The dispersion was stable and tended to form a film easily. After being left to stand for 48 hours, there was a large amount of sediment on the bottom which was simply redispersed by manually stirring the container.
[0151] Example 8
[0152] The graphene formulation of Example 3 was used to prepare an aqueous dispersion containing 58.4 wt % of the additive of the Example. 462.82 g of deionized water was placed in a container and the additive was added during stirring. 592.4 g of the additive was added. The dispersion was produced using a DISPERMAT CN 40 apparatus equipped with a VMA 60 Cowles head set to rotate at 4000 rpm. The additive was added in 5 batches of about 120 g each; after each addition of the additive, the disperser was rotated at 4000 rpm for 4 minutes. After the fifth addition, the disperser was rotated at 5500 rpm for 5 minutes.
[0153] Compared to Example 4, after each addition, a rich foam formed on the surface of the container which remained deposited prior to the subsequent addition.
[0154] The dispersion was stable and tended to form a film easily. After being left to stand for 48 hours, there was a large amount of sediment on the bottom which was simply redispersed by manually stirring the container.
[0155] Example 9
[0156] The formulations of Example 1, Example 3 and Example 6 were tested to evaluate their conductivity performance. The same test was performed on the original sulfur powder.
[0157] 3 grams of each of the three powders were compacted on a paper medium until a layer of compacted powder of approximately 4 mm was obtained.
[0158] The surface resistivity of the four samples was measured using an instrument Loresta-GX, MCP T700 with an ESP probe (MCP-TP08P).
[0159] The three formulations with graphene gave a surface resistivity of 10E+01 ohm / square, while sulfur was an insulator (>E+08).
[0160] Example 10
[0161] The graphene formulation of Example 4 and sulfur as received (ie, not mixed with graphene nanoplatelets) were subjected to quantification of resistivity.
[0162] In detail, the preparations with graphene were analyzed using the instrument Loresta-GX (Nittoseiko Analytech Co.), which allows the analysis of surface resistivity at 10 -4 Ω to 10 -7 In contrast, sulfur as a non-conductive material was analyzed using the instrument Hiresta-UX (Nittoseiko Analytech Co.), which can be used for samples with a surface resistivity of 10 3 Ω to 10 14 Samples in the Ω range.
[0163] In the case of both instruments, a PD-600 powder measurement system probe was used.
[0164] 7 g of the formulation with graphene was compacted at different pressures of 4 kN-8 kN-12 kN-16 kN and 20 kN. The compacted material was then subjected to surface resistivity analysis.
[0165] The same preparation as for the samples was carried out for the sulfur as received, but for this material 2 g of powder were sufficient to obtain the sample to be analyzed.
[0166] For both samples, the tests were performed in duplicate.
[0167] The formulations with graphene were very conductive for all tested pressures. On average, the samples exhibited a surface resistivity of 5.06E+01.
[0168] In contrast, as-received sulfur proved to be a non-conductive material with an average value of 2.65E+14 for all pressures.
Claims
1. A granular composition comprising: a) 50 to 95% by weight of sulfur; b) 5 to 50 wt % of graphene nanoplatelets; At least 90% of the graphene nanosheets have lateral dimensions (x, y) of 50 nm to 20,000 nm and a thickness (z) of 1 nm to 50 nm and a C / O ratio of ≥35:
1.
2. The granular composition according to claim 1, characterized in that It also contains 0.5 to 35 wt % of a binder.
3. Granular composition according to one or more of the preceding claims, characterised in that Contains digital electromagnetic sieve vibrator The vibration mode FTL0200 measures particulate matter with a particle size of 10 μm to 4000 μm.
4. Granular composition according to one or more of the preceding claims, characterised in that The binder is a wetting dispersant selected from the following: The content of the modified polyurethane is 100% of polyurethane oligomer and polyurethane polymer; Nonionic surfactants, including fatty acid ethoxylates, alcohol ethoxylates and ethoxylated sorbitan esters, preferably free of alkylphenol ethoxylates (APEO) and volatile organic compounds (VOCs), including sorbitan monooleate; Anionic surfactants, preferably free of alkylphenol ethoxylates (APEO) and volatile organic compounds (VOC); covering sodium polynaphthalene methane sulfonate, polymers with ethylene oxide, sodium polyphosphate, sodium salt of polyacrylic acid; Phosphate esters and their salts, including 6EO and 9EO tridecyl phosphate; Aldehyde and ketone resins; Epoxidized soybean oil; Polyethers modified with ester groups of phosphoric acid and its salts; Fatty acid modified polyesters; Polymers and copolymers having pigment-affinity groups, including modified polyethers having groups with high pigment affinity; 2,5-Furandione, telomers with 1,1'-(1,1-dimethyl-3-methylene-1,3-propanediyl)bis(benzene) and vinylbenzene, 3-(dimethylamino)propyl imide, imide with polyethylene glycol 2-aminopropyl Me ether, quaternized benzoate (salt) of 2-[(C10-16-alkoxy)methyl]oxirane; Sodium polycarboxylate; A mixture of 5-chloro-2-methyl-2H-isothiazol-3-one and 2-methyl-2H-isothiazol-3-one (CAS No. 55965-84-9).
5. A method for preparing a granular composition, the granular composition comprising: a) 50 to 95% by weight of sulfur; b) 5 to 50 wt% of graphene nanoplatelets having lateral dimensions (x, y) of 50 to 20,000 nm, a thickness (z) of 1 to 50 nm, and a C / O ratio of ≥ 35:1; c) optionally 0.5 to 35 wt % of a binder wherein the sulfur, the graphene nanosheets and optionally the binder are mixed in a turbine mixer device, the method being carried out at a temperature of 20°C to 150°C, the turbine mixer device being provided with at least one impeller wherein the blades rotate at a peripheral speed of 4m / sec to 50m / sec.
6. The method according to claim 5, characterized in that The turbine mixer device comprises: a rotating shaft equipped with 1 to 7 impellers mounted in series on the rotating shaft; and a heating and / or cooling jacket for controlling temperature.
7. The method according to claim 5 or 6, characterized in that This is performed for a total time of 5 minutes to 60 minutes.
8. A dispersion of a granular composition according to one or more of claims 1 to 6 in a liquid selected from water and organic solvents.
9. Use of the granular composition according to one or more of claims 1 to 4 or the dispersion according to claim 8 for producing a battery cathode.
10. A battery cathode comprising the granular composition according to one or more of claims 1 to 4.
Citation Information
Patent Citations
Production of nano-structures
EP2038209B1
Continuous process for preparing pristine graphene nanoplatelets
EP3157864B1
Process for preparing graphene nanoplatelets
EP3157865B1